The Role of Telesom’s ZAAD Service in Sustainable Finance in Somaliland’s Telecommunications Sector - Abdihakin Mohamoud Ibrahim (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This paper examines how Somaliland’s liberalized, privately led telecommunications sector, once a state monopoly and now dominated by local firms, has become a driver of economic growth, financial inclusion, and infrastructure development, with Telesom as the leading example. Drawing on sectoral history, market composition, and coverage data, the study shows how Telesom and its competitors have built nationwide networks, delivered low-cost services, and enabled mobile money-based financial services in the context of weak formal banking. Focusing on Telesom’s ZAAD platform, the paper analyzes its ecosystem business model (salary payments, merchant networks, and high-frequency transactions), its contribution to financial inclusion, and its alignment with international anti–money laundering and customer due diligence standards. At the same time, it identifies ethical and prudential gaps, especially the absence of formal deposit protection, limited transparency in financial reporting and taxation, and the lack of an independent telecommunications regulator, which pose risks to consumers and systemic stability. Overall, the paper argues that Telesom illustrates how sustainable finance in telecommunications can combine innovation, inclusion, and profitability, provided that stronger governance, disclosure, and consumer protection frameworks are implemented to secure long-term sector resilience.